2008
DOI: 10.1029/2007jd009391
|View full text |Cite
|
Sign up to set email alerts
|

Coupled chemistry climate model simulations of the solar cycle in ozone and temperature

Abstract: [1] The 11-year solar cycles in ozone and temperature are examined using new simulations of coupled chemistry climate models. The results show a secondary maximum in stratospheric tropical ozone, in agreement with satellite observations and in contrast with most previously published simulations. The mean model response varies by up to about 2.5% in ozone and 0.8 K in temperature during a typical solar cycle, at the lower end of the observed ranges of peak responses. Neither the upper atmospheric effects of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
225
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(259 citation statements)
references
References 71 publications
29
225
5
Order By: Relevance
“…Transitioning from SCmin to SCmax leads to a constant increase of~5 DU in the equatorial TCO [Randel and Wu, 2007]. The change in the equatorial TCO due to the solar forcing is therefore a combination of both dynamical and photochemical processes and exhibits a double-peak structure in the lower and the upper stratosphere [Hood, 1997;Kodera and Kuroda, 2002;Matthes et al, 2006;Soukharev and Hood, 2006;Austin et al, 2008;Hood and Soukharev, 2012]. Results obtained using the ERAI TCO are qualitatively the same, except the equatorial TCO change from SCmin/eQBO to SCmax/eQBO that is slightly less than the MOD TCO.…”
Section: Resultssupporting
confidence: 66%
“…Transitioning from SCmin to SCmax leads to a constant increase of~5 DU in the equatorial TCO [Randel and Wu, 2007]. The change in the equatorial TCO due to the solar forcing is therefore a combination of both dynamical and photochemical processes and exhibits a double-peak structure in the lower and the upper stratosphere [Hood, 1997;Kodera and Kuroda, 2002;Matthes et al, 2006;Soukharev and Hood, 2006;Austin et al, 2008;Hood and Soukharev, 2012]. Results obtained using the ERAI TCO are qualitatively the same, except the equatorial TCO change from SCmin/eQBO to SCmax/eQBO that is slightly less than the MOD TCO.…”
Section: Resultssupporting
confidence: 66%
“…A questions arises here as whether the ozone changes in the TLS associated with radiatively forced temperature changes via temperature dependence of photolysis rates. Austin et al [14] concluded from their analysis that the tropical upper stratospheric ozone anomalies are radiatively driven while those in the TLS are driven indirectly by changes in advection (tropical ascent driven by extratropical wave forcing). Gray et al [38] similarly suggested that the TLS ozone response is due to dynamical redistribution.…”
Section: Ozone and Temperature Feedbacks To Solar Variationsmentioning
confidence: 99%
“…The common method to simulate the solar cycle is to include either changes in total solar irradiance (TSI) or changes in UV radiation to account for ozone changes through photochemistry. Recently developed chemistry-climate models (CCMs) can incorporate ozone feedbacks to solar variation [19] and some of these models can simulate the solar response in ozone and temperatures reasonably well [14]. Merkel et al [20] found that the ozone response is caused by the photochemistry related to the UV variability and if the UV has a small magnitude of the variability then the ozone will has a small response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the variations of the total solar irradiance (TSI) cannot be the reason for the increase of the mean global temperature over the past 20 years (Lockwood & Fröhlich 2007), the variations of the solar spectral irradiance (SSI) are considered to have an effect on the Earth's climate system. For example, Egorova et al (2004), and Austin et al (2008) demonstrate that the Earth's atmosphere shows an effect on the solar cycle variability in the UV spectral range. The effect of a longterm trend of the solar spectral variability on the Earth's climate system are however not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%